ANALISIS DAMPAK EKONOMI KUNJUNGAN WISATA RELIGI KAWASAN SEKUMPUL TERHADAP PENGEMBANGAN EKONOMI LOKAL (STUDI PADA MAKAM GURU SEKUMPUL, MARTAPURA KAB. BANJAR) - Nurhalisa Aulia; Noor Rahmini (PPJP Universitas Lambung Mangkurat, 2020)
This Research was conducted to find out how he economic impact of tourism on the economic development of local communities and how the role of the community towards the existence of religius tourism. The research method used is descriptive qualitative.The results of analiysis in the study can be obtained that the direct, indirect and follow-up economic felt by local communities. Dicert economic impacts include rental shops, clothing stores, dining places and parking. The indirect economic impact include transportation and lodging services. The following impacts include road access and the potensial for the other religious tourism. The role of the community towards the existence of religious tourism is the involvement of the community in terms of regional cleanliness, calm and religious activities carried out long ago. Keywords: Tourism, Direct Economic Impact, Indirect Economic Impacts, Adverse Impacts